2020
DOI: 10.3390/ani10020238
|View full text |Cite
|
Sign up to set email alerts
|

The Biodegradation Role of Saccharomyces cerevisiae against Harmful Effects of Mycotoxin Contaminated Diets on Broiler Performance, Immunity Status, and Carcass characteristics

Abstract: A feeding trial (35 days) was carried out to investigate the effect of Saccharomyces cerevisiae cell wall as a mycotoxin biodegradation agent on the performance, feed efficiency, carcass traits, and immunity response against diseases in broilers fed aflatoxin B1 contaminated diets. For this purpose, 200 one day old broilers were randomly allotted into four groups, each with five replicates (10 birds per replicate). Four starter and finisher experimental rations were formulated by using (A) 0, (B) 1.25, (C) 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 46 publications
(54 reference statements)
5
38
0
Order By: Relevance
“…Previous studies have reported that stress affects the secretion of LH and FSH in turkey poults [40], laying hens [8,41], and turkey hens [42]. Thus, successful and profitable poultry production requires understanding the negative effects of environmental conditions and overcoming them [43,44]. M. oleifera could be used as a valuable feed additive in animal nutrition due to its unique nutritional profile [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported that stress affects the secretion of LH and FSH in turkey poults [40], laying hens [8,41], and turkey hens [42]. Thus, successful and profitable poultry production requires understanding the negative effects of environmental conditions and overcoming them [43,44]. M. oleifera could be used as a valuable feed additive in animal nutrition due to its unique nutritional profile [21].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the seeds of Moringa oleifera are a source of protein, iron, calcium, ascorbic acid vitamin A, and antioxidant compounds, such as carotenoids, flavonoids, vitamin E, and phenolics [46]. The presence of vitamins and minerals benefit the immune system and cure a myriad of diseases [19,43,44,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…The small intestine was measured between the site from which the duodenum emerges from the gizzard and the beginning of the ceca. The relative organ weight was calculated according to Arif et al [42] formula: the relative organ weight = (weight of organ/live weight of bird) × 100.…”
Section: Intestine Morphometric Analysis and Lesions Scorementioning
confidence: 99%
“…Body weights (BW), weight gain (WG), and feed intake (FI) were recorded at 14 and 49 days of age in early morning before receiving any feed. FCR was also calculated as described by Arif et al [30]. On 49 days, after 12 h of feed deprivation, five birds per group, one bird/replicate/group, were randomly selected, weighed, slaughtered, scalded, wet-plucked, and eviscerated.…”
Section: Growth Performance Traitsmentioning
confidence: 99%